The dynamics of coercion and fear in "Where are you going, where have you been?": a story by Joyce Carol Oates - Mancelos, João de (2013)
“Where Are You Going, Where Have You Been?” (1966) is Joyce Carol Oates’s most celebrated and anthologized short story. The tense plot presents a young man, Arnold Friend, who tries to convince Connie Wyatt, a fifteen-year-old girl, to join him for a car ride. Connie declines, feeling there is something wrong with him. Thwarted by Connie’s repeated refusals and excuses, Friend becomes increasingly more threatening. The tense dialogue that occurs between both characters shows the power of coercion and the strategies it resorts to: (1) trickery, (2) manipulation, and (3) threat. At the same time, thanks to Connie, the reader becomes aware of the different responses to coercion. There is a well-structured crescendo that includes (1) anxiety, (2) fear, (3) panic and (4) submission. In this paper I intend to analyze (1) the dynamics of coercion and fear, (2) different strategies used in the process of coercion, (3) several responses to threat, (4) how they are represented in this story, to create suspense. To substantiate my nalysis, I resort to the studies of several specialists in the field of gothic literature, criminal psychology, and, naturally, to my own opinions.